Attitudes toward COVID-19 vaccination and willingness to pay: comparison of people with and without mental disorders in China. Issue 5 (11th September 2021) - Hao, Fengyi; Wang, Bokun; Tan, Wanqiu; Husain, Syeda Fabeha; McIntyre, Roger S.; Tang, Xiangdong; Zhang, Ling; Han, Xiaofan; Jiang, Li; Chew, Nicholas W. S.; Tan, Benjamin Yong-Qiang; Tran, Bach; et al.
Abstract : Background: Acceptance and willingness to pay for the COVID-19 vaccine are unknown. Aims: We compared attitudes toward COVID-19 vaccination in people suffering from depression or anxiety disorder and people without mental disorders, and their willingness to pay for it. Method: Adults with depression or anxiety disorder ( n = 79) and healthy controls ( n = 134) living in Chongqing, China, completed a cross-sectional study between 13 and 26 January 2021. We used a validated survey to assess eight aspects related to attitudes toward the COVID-19 vaccines. Psychiatric symptoms were assessed by the 21-item Depression, Anxiety and Stress Scale. Results: Seventy-six people with depression or anxiety disorder (96.2%) and 134 healthy controls (100%) reported willingness to receive the COVID-19 vaccine. A significantly higher proportion of people with depression or anxiety disorder (64.5%) were more willing to pay for the COVID-19 vaccine than healthy controls (38.1%) ( P ≤ 0.001). After multivariate adjustment, severity of depression and anxiety was significantly associated with willingness to pay for COVID-19 vaccination among psychiatric patients ( P = 0.048). Non-healthcare workers ( P = 0.039), health insurance ( P = 0.003), living with children ( P = 0.006) and internalised stigma ( P = 0.002) were significant factors associated with willingness to pay for COVID-19 vaccine in healthy controls. Conclusions: To conclude, psychiatric patients in Chongqing, China, showed high acceptance and willingness to pay for the COVID-19 vaccine. Factors associated with willingness to pay for the COVID-19 vaccine differed between psychiatric patients and healthy controls.